2017
DOI: 10.1007/s00404-017-4503-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between the number of oocytes retrieved and cumulative live birth rate in women aged 35–40 years undergoing long GnRH agonist IVF/ICSI cycles

Abstract: The ideal number of oocytes retrieved in women aged 35-40 years is 10-14 oocytes, which achieves a high cumulative LBR while maintaining an acceptable low OHSS rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…The authors concluded that the low response patient with a mean age of 31 years (1–3 oocytes) had a significantly lower cumulative LBR (22%) compared to other sub-groups, including the suboptimal response patient (4–9 oocytes) in whom the cumulative LBR was 40% and the optimal response patient (10–15 oocytes) for whom the cumulative LBR was 51%. These findings were recently corroborated by Zhou et al (2017) in patients aged 35–40 years [ 29 ]. Again, the low response patient (1–4 oocytes) had the lowest cumulative LBR (37%) as compared to other sub-groups.…”
Section: One More Oocyte Matterssupporting
confidence: 70%
“…The authors concluded that the low response patient with a mean age of 31 years (1–3 oocytes) had a significantly lower cumulative LBR (22%) compared to other sub-groups, including the suboptimal response patient (4–9 oocytes) in whom the cumulative LBR was 40% and the optimal response patient (10–15 oocytes) for whom the cumulative LBR was 51%. These findings were recently corroborated by Zhou et al (2017) in patients aged 35–40 years [ 29 ]. Again, the low response patient (1–4 oocytes) had the lowest cumulative LBR (37%) as compared to other sub-groups.…”
Section: One More Oocyte Matterssupporting
confidence: 70%
“…The probability of each individual existing is very low. Each human comes from one spermatozoon out of approximately 200 million [13], that merges with one of approximately 300 thousand potential ovules [14]. To this, we add the improbability that the parents of that individual existed, and also their grandparents, great grandparents, and so on, for generations.…”
Section: Who Are We?mentioning
confidence: 99%
“…In other studies, some researchers also observed that the optimal number of oocytes retrieved for good CLBR and avoiding severe OHSS was 6-15 in the GnRH-antagonist protocols of non PCOS patients [9]. However, the ideal number of oocytes retrieved was 10-14 in another study of women aged 35-40 [28]. At the same time, there was a signi cant positive correlation between the number of oocytes retrieved and CLBR in a retrospective analysis of IVF-ET treatment in PCOS patients.…”
Section: Discussionmentioning
confidence: 94%